CLINICAL STUDY OF UDAVARTINI (DYSMENORRHEA) YONIVYAPATH WITH ORAL ADMINISTRATION OF JEERAKADIMODAKA AND RASNADITAILA MATRAVASTI - lakshmi, Harita; Vijayalakshmi, B.; Subbalaxmi, B. (International Journal of Ayurveda and Pharma Research, 2015)
Udavartini (Dysmenorrhea) is one of the most common clinical problem observed in regular practice. Dysmenorrhea is a medical condition of pain during menstruation that interferes with daily activities, as defined by ACOG and others. Dysmenorrhea can be correlated with Udavartini Yonivyapad in Ayurveda. The treatment of this disorder is still unsatisfactory in modern medicine, as the usage of anti spasmodic drugs, hormones may cause many side effects like hypertension, psychological disturbances etc. An attempt has been made to treat this condition with Ayurvedic system of medicine. So a research work has been carried out to study the efficacy of Jirakadi Modaka oral administration and Matravasti with Rasnadi tailam. 50 patients with Udavartini yonivyapat diseases were selected randomly and the drug was administered for the period of 90 days. Encouraging results were observed with the trial drug and the intensity of pain and the successive cycles were less painful. Vasti is considered best treatment for controlling Vata and the orally administered drug Jirakadi Modaka (Bhavaprakasha) has Vedanasthapana, Vaatahara, Anulomana and Rasayana properties. The present study Jeerakadi Modaka orally and Rasnadi tailam Matra vasti combine acts against Udavartini and is highly effective.